1980
DOI: 10.1017/s0014479700012047
|View full text |Cite
|
Sign up to set email alerts
|

Yield Stability Studies in Soyabeans (Glycine Max)

Abstract: SUMMARYRegression analysis, stability variance method, and the genotype-grouping technique were used to investigate the relative yield stability of 20 soyabean genotypes, grown in 12 diverse environments in Malaysia in 1978. With the regression analysis, four genotypes were observed to be unstable for grain yield; however, for the remaining 16 genotypes with non-significant regression coefficients, a substantial proportion of the g × e interaction was non-linearly related to the environmental indices. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…73 In different studies, Francis and Kannenberg 72 method was found most useful and informative compared with other stability parameters. 34,74,75 A positive correlation was also found between b i and CV. 41 Coefficient of determination:…”
Section: Joint Regression and Qtl Mappingmentioning
confidence: 86%
“…73 In different studies, Francis and Kannenberg 72 method was found most useful and informative compared with other stability parameters. 34,74,75 A positive correlation was also found between b i and CV. 41 Coefficient of determination:…”
Section: Joint Regression and Qtl Mappingmentioning
confidence: 86%
“…its variance among environments is zero" (Becker and Léon 1988). ANOVA analysis, standard deviation and coefficient of variation have been used to test how genotypes vary across environments (Perkins and Jinks 1968, Francis and Kannenberg 1978, Funnah and Mak 1980, Ngeve and Bouwkamp 1993.…”
Section: Use Of Different Statistical Methods To Assess Stability In mentioning
confidence: 99%
“…The simplicity of the procedure makes it versatile in its application. Funnah and Mak (1980) also found it to be very convenient in their work with soybean.…”
Section: Locationmentioning
confidence: 98%
“…Several workers (Ayuk-Takem, 1981;Bacusmo et al, 1988;Crossa, 1988;Funnah and Mak, 1980;Jowett, 1972;Kang and Miller, 1984) have compared methods of stability analyses to study the usefulness of the different procedures for their specific data. Jowett (1972) compared the methods of Eberhart and Russell (1966), Finlay and Wilkinson (1963) and Wricke (1962) in a study of yield stability among sorghum [Sorghum bicolor (L.) Moench] inbred lines in East Africa and found Wricke's method, based on ecovalence, cumbersome and the least informative of the three methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation